Research on traffic identification and wavelength scheduling scheme in optical internet - WANG Hong-xiang; JI Yue-feng; LI Hui (Tongxin xuebao)
A conception of universal inter-arrival time （UIAT）, and a traffic identification algorithm based on UIAT by using Bayesian network was presented. A novel wavelength scheduling scheme with traffic identification was proposed and numerically simulated. Simulation results show, the average traffic identification accuracy of the method is higher than 98%, and the identification accuracies vary with the number of instances of that traffic in the training data. It is also shown that the traffic identification based wavelength scheduling scheme can match the wavelength utilization with ap-plication requirements better with higher wavelength efficiency.